Mysteries of mind, space & time the unexplained. (Westport, Conn. H.S. Stuttman, 1992)
A twenty-six-volume study of the paranormal, mystical, and psychic phenomena commonly referred to as the supernatural.
Expanded ed. of: The unexplained. Reference ed. 1986.
Includes bibliographical references and index.
Keywords: Curiosities and wonders; Supernatural; Supernatural -- Encyclopedias; Occultism -- Encyclopedias